Collective Memory in P. Everett’s Novel “I Am Not Sidney Poitier” - HCHEPACHEVA, I.V.; KARASIK, O.B.; OSOVSKY, O.E. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article deals with one of Percival Everett’s latest novels. In his novel, he addresses an image of Sydney Poitier who was an icon of the 60s of the 20th century, one of the representatives of the movement for the rights of African Americans in the USA. The authors of the article conclude that the novel has the same plot structures as movies that Sydney Poitier starred. The main aim of appealing to the film heritage is to present traditional views and prejudices of American society towards racial discrimination and slavery, identity, and race. RESUMEN Este artículo trata de una de las últimas novelas de Percival Everett. En su novela, aborda una imagen de Sydney Poitier, quien fue un ícono de los años 60 del siglo XX, uno de los representantes del movimiento por los derechos de los afroamericanos en los Estados Unidos. Los autores del artículo llegan a la conclusión de que la novela tiene las mismas estructuras argumentales que las películas protagonizadas por Sydney Poitier. El objetivo principal de apelar al patrimonio cinematográfico es presentar los puntos de vista y prejuicios tradicionales de la sociedad estadounidense hacia la discriminación racial y la esclavitud, la identidad y la raza.